Freestanding, Fiber‐Based, Wearable Temperature Sensor with Tunable Thermal Index for Healthcare Monitoring. Issue 12 (11th May 2018) - Trung, Tran Quang; Le, Hoang Sinh; Dang, Thi My Linh; Ju, Sanghyun; Park, Sang Yoon; Lee, Nae‐Eung
Abstract: Fiber‐based sensors integrated on textiles or clothing systems are required for the next generation of wearable electronic platforms. Fiber‐based physical sensors are developed, but the development of fiber‐based temperature sensors is still limited. Herein, a new approach to develop wearable temperature sensors that use freestanding single reduction graphene oxide (rGO) fiber is proposed. A freestanding and wearable temperature‐responsive rGO fiber with tunable thermal index is obtained using simple wet spinning and a controlled graphene oxide reduction time. The freestanding fiber‐based temperature sensor shows high responsivity, fast response time (7 s), and good recovery time (20 s) to temperature. It also maintains its response under an applied mechanical deformation. The fiber device fabricated by means of a simple process is easily integrated into fabric such as socks or undershirts and can be worn by a person to monitor the temperature of the environment and skin temperature without interference during movement and various activities. These results demonstrate that the freestanding fiber‐based temperature sensor has great potential for fiber‐based wearable electronic platforms. It is also promising for applications in healthcare and biomedical monitoring. Abstract : A freestanding, wearable, fiber‐based temperature sensor is presented, which can easily be integrated into clothing such as socks and undershirts and can be worn by a person to monitor the temperature of the environment around the person and the temperature of the person without interference from movement and activity. This sensing device has great potential for next‐generation wearable electronics.